Pre-collisional extensional tectonics in convergent continental margins: the cretaceous evolution of the central cordillera of the Colombian Andes (2015)
The Cretaceous tectonic evolution of the Northern Andes continental margin is characterized by continuous convergence that allowed the formation of continental volcanic arcs, back arc basins, extensional divergent tectonics and accretion of exotic terranes. Such a record, particularly the extensional phases, is commonly hidden by the overimposition of deformational events associated with evolution of the subduction configuration, collision of exotic terranes and strike slip fragmentation. We integrate field geology, stratigraphy, U-Pb provenance and geochronology to improve the understanding of the Early Cretaceous pre-deformation phases in the western flank of the Central Cordillera and to refine the understanding of Cretaceous to Early Paleogene paleo-tectonic evolution. Lower Cretaceous sedimentation was deposited over Triassic metamorphic units and includes a transgressive record characterized by fan delta conglomerates overlaid by distal turbidities and a syn-sedimentary volcanic record at 100 ma. This record is related to continental crust extension and sea floor spreading that formed ribbons and microcontinents separated by oceanic crust. Following this extensional event, an 85 – 82 Ma two-arc system seems to have been formed over the main continental margin and an isolated microcontinent. These two arcs collided and were also juxtaposed to another allochthonous Cretaceous oceanic arc between 80 Ma and 60 Ma.